Vocational College teachers in Malaysia: emotional intelligence - Mustafa, Mohamad Zaid; Nordin, Mohd Norazmi; Abdul Razzaq, Abdul Rasid; Ibrahim, Badaruddin (2020)
This study aimed to validate factors related to emotional intelligence that influence organizational commitment among vocational college teachers in Malaysia. To this day, the issue of emotional intelligence remains a major cause of teacher commitment to their organization, especially among vocational college teachers. Studies have found that self-awareness, self-management, social awareness and relationship management are key elements in emotional intelligence that influence the organizational commitment of vocational college teachers in Malaysia. Therefore, this quantitative study was conducted to confirm the elements related to emotional intelligence. The questionnaire was administered to 264 vocational college teachers in Malaysia randomly. The data obtained were then analyzed using Structural Equation Modelling (SEM) using AMOS 21 application. Confirmatory Factor Analysis was performed to obtain factor loading for each element obtained namely self-awareness, self-management, social awareness and relationship management. The analysis results show that the factors reflect the appropriate fit and meet all the criteria for validation.